Simulating security of supply effects of the Nabucco and South Stream projects for the European natural gas market - Caroline Dieckhöner (Institute of Energy Economics at the University of Cologne (EWI), 2010)
Due to the increasing European import dependency, significant additional natural gas volumes will be required. In addition to the Nord Stream pipeline, the Nabucco and South Stream pipeline are projects planned for the next decade to provide further gas supplies to the European market. As one of the European Union's energy policies' foci is security of supply, the question can be raised if and how these projects contribute to this objective not only in terms of diversification but also in case of supply disruptions such as occurred in 2009 during the Russia-Ukraine gas crisis. This paper discusses the impact of these two major gas import pipeline projects on the South-Eastern Europe gas supply and analyzes their effects on gas flows and marginal cost prices in general and in case of gas supply disruptions via Ukraine in a model-based analysis with the European natural gas infrastructure and dispatch model TIGER.
Keywords: L95; C61; Q41; Q34; 330; Natural gas; security of supply; Nabucco; South Stream; Europe; linear-optimization; transport infrastructure; Erdgasmarkt; Energieversorgung; Gasleitungstransport; Südosteuropa; EU-Staaten